Effectiveness of Training Programs in Increase Motivation Soldier Battalion 611 Awang Long Infantry - Muhammad Daffa Fadhila; Abshor Marantika (Dinasti International Journal of Education Management and Social Science, 2025)
Motivation in Battalion Infantry 611/Awang Long plays an important role in increasing soldiers’ performance and discipline. A systematic training program functioning For strengthen skills, building trust self and solidarity between soldiers, so that increase readiness face challenges. The study shows that training provided by the commander can motivate soldiers, although there are still difficulties in implementation. Material training covers various skills military , aims produce soldier professional and disciplined. This study aims to identify factors that influence soldier motivation Battalion Infantry 611/Awang Long, Analyzing effectiveness of training program strategies in increase motivation soldier,Analyze impact improvement motivation to performance soldiers in the field . The results found in study This is Motivation soldier Battalion Infantry 611/Awang Long is affected by the fulfillment need basis , hope will results , and reinforcement positive . Training program effective can increase motivation , discipline , and performance soldier with combine theory motivation classic and modern. Training should considered as part from management strategic source Power man military , which contributes to professionalism and morality soldier . Research This emphasize importance notice aspect psychological , social , and physical in designing training programs For increase motivation soldier. Study This give contribution new in development source Power man military with introduce approach more comprehensive For increase motivation and performance soldier.